2015
DOI: 10.1095/biolreprod.114.126227
|View full text |Cite
|
Sign up to set email alerts
|

A Role of sFlt-1 in Oxidative Stress and Apoptosis in Human and Mouse Pre-Eclamptic Trophoblasts1

Abstract: Pre-eclampsia (PE) is a hypertensive disorder that occurs during pregnancy, and is a multifactorial disease. The antiangiogenic factor, soluble fms-like tyrosine kinase 1 (sFlt-1), has been reported to be important in the pathogenesis of PE, but the mechanism of its involvement remains unknown. To test the effects of sFlt-1 on pregnancy, we injected pregnant mice with exogenous mouse sFlt-1. After 18 days of gestation, higher blood pressure, proteinuria, and histological differences were observed compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 33 publications
(40 reference statements)
4
23
0
Order By: Relevance
“…Other animal models of HTN-Preg show increased or unchanged circulating levels of sFlt-1 (Agunanne et al, 2010; Ramesar et al, 2011; Sunderland et al, 2011; Siddiqui et al, 2013; Bobek et al, 2015; Gillis et al, 2015). Importantly, pregnant rats treated with exogenous sFlt-1 develop HTN, proteinuria, marked glomerular endotheliosis with occlusion of renal capillaries and focal fibrin deposition in glomerular cells (Maynard et al, 2003; Holwerda et al, 2014; Jiang et al, 2015). Also, mice treated with sFlt-1 show an increase in the vascular response to ET-1 (Amraoui et al, 2014).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%
“…Other animal models of HTN-Preg show increased or unchanged circulating levels of sFlt-1 (Agunanne et al, 2010; Ramesar et al, 2011; Sunderland et al, 2011; Siddiqui et al, 2013; Bobek et al, 2015; Gillis et al, 2015). Importantly, pregnant rats treated with exogenous sFlt-1 develop HTN, proteinuria, marked glomerular endotheliosis with occlusion of renal capillaries and focal fibrin deposition in glomerular cells (Maynard et al, 2003; Holwerda et al, 2014; Jiang et al, 2015). Also, mice treated with sFlt-1 show an increase in the vascular response to ET-1 (Amraoui et al, 2014).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%
“…Mitochondrial activity is essential in pregnancy because it sustains the metabolic activity of the placenta throughout gestation (LaMarca et al, 2008 ). Recently, a potential association between increased soluble anti-angiogenic factors levels and mitochondrial dysfunction has been suggested (Jiang et al, 2015 ). Exogenous administration of sFlt-1 in pregnant mice have shown to induce placental mitochondrial swelling, oxidative stress and apoptosis in trophoblasts (Jiang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a potential association between increased soluble anti-angiogenic factors levels and mitochondrial dysfunction has been suggested (Jiang et al, 2015 ). Exogenous administration of sFlt-1 in pregnant mice have shown to induce placental mitochondrial swelling, oxidative stress and apoptosis in trophoblasts (Jiang et al, 2015 ). In addition, preeclamptic plasma mediators induced deleterious effects on mitochondrial function of human umbilical vein endothelial cells (HUVEC) (McCarthy and Kenny, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…reported that in the serum of sFLT-1 treated preeclamptic mice, oxidant malonyl dialdehyde levels were higher and antioxidant superoxide dismutase levels were lower when compared with controls (23). Hence, they suggested that sFLT-1 promoted apoptosis by increasing oxidative stress.…”
Section: Discussionmentioning
confidence: 96%